Contract Nonperformance and Ambiguity in Insurance Markets - Andreas Landmann; Christian Biener; Martin Eling; Maria Isabel Santana (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Insurance contract nonperformance relates to situations when valid claims are not paid by the insurer. We extend probabilistic insurance models to allow for such nonperformance risk as well as ambiguity regarding nonperformance and loss probabilities. We empirically test theoretical predictions from our model within a field lab experiment in a low-income setting. This is a persuasive context, since especially in emerging and poorly regulated markets there is a higher chance of contract nonperformance. In line with our predictions, insurance demand decreases by 17 percentage points in the presence of contract nonperformance risk and is reduced by a further 14 percentage points when contract nonperformance risk is ambiguous. It also seems that ambiguity does not easily disappear with experience. The results have implications for both industrialized and developing insurance markets.
Keywords: C91; D81; G22; 330